2022
DOI: 10.3389/fmars.2021.782734
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metal Dynamics in Shallow Hydrothermal Plumes at the Kermadec Arc

Abstract: Hydrothermal vents are a source of many trace metals to the oceans. Compared to mid-ocean ridges, hydrothermal vent systems at arcs occur in shallower water depth and are much more diverse in fluid composition, resulting in highly variable water column trace metal concentrations. However, only few studies have focused on trace metal dynamics in hydrothermal plumes at volcanic arcs. During R/V Sonne cruise SO253 in 2016/2017, hydrothermal plumes from two hydrothermally active submarine volcanoes along the Kerma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 98 publications
1
13
0
Order By: Relevance
“…(e.g., El Hierro) (Fraile-Nuez et al, 2012). Hydrothermal plume sampling protocols and analytical methods are detailed in Kleint et al (2022).…”
Section: Expected Results-discussionmentioning
confidence: 99%
“…(e.g., El Hierro) (Fraile-Nuez et al, 2012). Hydrothermal plume sampling protocols and analytical methods are detailed in Kleint et al (2022).…”
Section: Expected Results-discussionmentioning
confidence: 99%
“…Samples presented here are from the northwest side of the caldera and the caldera upper wall, as well as the northward-propagating plume from this end of the caldera (Kleint et al, 2019(Kleint et al, , 2022Neuholz et al, 2020). Vents at this site are characterized by high temperatures ($300 °C), low pH (pH % 3) and high Fe:H 2 S ratios (up to >10) (Kleint et al, 2019(Kleint et al, , 2022. The neutrally buoyant plume is diluted with ambient seawater > 10 2 times within days (Neuholz et al, 2020).…”
Section: Hydrothermal Influencementioning
confidence: 99%
“…However, this site is much shallower than the observed [Fe] plume along the GP13 transect and, given the high degree of heterogeneity along the southern Kermadec Arc, may differ chemically from the source of the [Fe] plume seen along GP13. While still considerably variable, hightemperature vent fluids from volcanoes at > 1000 m depth along the southern Kermadec Arc generally show [Fe] > [H 2 S], and total dissolved Fe > [Fe(II)] ( Kleint et al, 2019Kleint et al, , 2022, with Fe(III) oxides important at some sites for metal transport within the plume (Kleint et al, 2022).…”
Section: Hydrothermal Influencementioning
confidence: 99%
See 1 more Smart Citation
“…Modelling has shown that upwelling of hydrothermal Fe might be responsible for 15-30% of the primary production in this region, thus linking the global biogeochemical cycles of iron and carbon. Iron from shallow hydrothermal plumes at the Tonga-Kermadec Arc is an important component of increased nitrogen fixation and primary production in that region 224,225 .…”
Section: Ironmentioning
confidence: 99%